2019
DOI: 10.1371/journal.ppat.1007533
|View full text |Cite
|
Sign up to set email alerts
|

A high rate of polymerization during synthesis of mouse mammary tumor virus DNA alleviates hypermutation by APOBEC3 proteins

Abstract: Retroviruses have evolved multiple means to counteract host restriction factors such as single-stranded DNA-specific deoxycytidine deaminases (APOBEC3s, A3s). These include exclusion of A3s from virions by an A3-unreactive nucleocapsid or expression of an A3-neutralizing protein (Vif, Bet). However, a number of retroviruses package A3s and do not encode apparent vif - or bet -like genes, yet they replicate in the presence of A3s. The mode by which they overcome del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Previous data from studies of mA3-insufficient mice indicated that MMTV replication and tumorigenesis are inhibited by members of the Apobec family of cytidine deaminases (12). No MMTV-specified inhibitors of these enzymes have been reported, including in a recent report that concluded on the basis of transfection experiments in 293T cells that MMTV does not encode an mA3 inhibitor (54). Our experiments are consistent with the need for Rem C-terminal sequences to antagonize the mutagenic effects of the Apobec cytidine deaminase AID during MMTV replication in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data from studies of mA3-insufficient mice indicated that MMTV replication and tumorigenesis are inhibited by members of the Apobec family of cytidine deaminases (12). No MMTV-specified inhibitors of these enzymes have been reported, including in a recent report that concluded on the basis of transfection experiments in 293T cells that MMTV does not encode an mA3 inhibitor (54). Our experiments are consistent with the need for Rem C-terminal sequences to antagonize the mutagenic effects of the Apobec cytidine deaminase AID during MMTV replication in lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…As described above, Vif is a well-studied viral protein that counteracts host APOBEC3 proteins. Other than Vif, some viral proteins such as HIV-1 protease [ 68 ] and RT [ 69 ], FIV protease [ 57 ], murine leukemia virus protease [ 70 ] and glycogag [ 71 ], human T-cell leukemia virus type I capsid [ 72 ], and mouse mammary tumor virus RT [ 73 ] potentially counteract host antiviral APOBEC3 proteins. These observations suggest that retroviruses have evolved a variety of strategies to counteract APOBEC3 proteins.…”
Section: Apobec3 Proteins and Non-retrovirusesmentioning
confidence: 99%
“…In a second study, a different group suggested that MMTV evolved its reverse transcriptase for a high polymerization rate to escape mA3 hypermutation during cDNA synthesis [301]. Using cell culture and overexpression experiments, Hagen et al showed that MMTV packaged the same levels of human A3G or mA3 as HIV-1 lacking Vif expression (HIV-1-ΔVif).…”
Section: Betaretroviruses and Deamination-independent Apobec Activitymentioning
confidence: 99%